Strategi Pemanfaatan Sarana Prasarana dan Pendapatan Ojek Online Terhadap Kesejahteraan Keluarga (Studi kasus para Ojek Online di Pangkalan BTC Mall Bekasi) - Abdilah; Aditya Perarie; Rustomo; Pristanto Ria Irawan (Journal of Mandalika Literature, 2025)
Transportation is a necessity in the current era, one of the transportation services that is currently experiencing rapid development, namely becoming an online motorcycle taxi driver, including the drivers at the BTC Mall Bekasi online motorcycle taxi base. Competence and experience in a job are indispensable in the case of online motorcycle taxi drivers, namely how drivers master, understand, are intelligent and educated in terms of using applications as a means of supporting income. This study examines the effect of Utilization of Infrastructure on Family Welfare, the effect of Income on Family Welfare and the study of the two independent variables on the dependent variable. Using a quantitative description method to explain the relationship and influence of two independent variables on the dependent variable. The research instrument with a questionnaire on a linked scale was given to 32 online motorcycle taxi drivers as respondents. The results of research on the use of online motorcycle taxi infrastructure and income on family welfare, the data are declared valid and reliable and partially infrastructure affects family welfare but has a low relationship and is declared not to contribute directly, but income has a relationship and has a significant effect on family welfare with a moderate correlation, and tested simultaneously on 3 variables showing that the two independent variables have a positive effect and have a significant relationship between the variables of infrastructure and income together with family welfare.